Polycystic ovary syndrome in adolescents with obesity - Fu,Leyi (2021)
SUMMARY INTRODUCTION: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age with the prevalence from 5% to 15%, and the prevalence of PCOS in adolescents with obesity seems even higher. The weight status is significantly associated with the quality of life in adolescents with PCOS. OBJECTIVE: This review aims to summarize the latest findings of pathogenesis, diagnosis, comorbidity, and management in PCOS adolescents with obesity. METHODS: This is a narrative review of articles published in PubMed from June 2013 to June 2020 Data were searched using the key words of “polycystic ovary syndrome” AND “adolescent” AND “obesity.” RESULTS: Pubertal obesity, particularly central obesity, could have a negative impact on the pathophysiology of PCOS. In adolescents with obesity, a review of medical history and a long-term follow-up for PCOS symptoms are essential to avoid misdiagnosis. There is a link between obesity and comorbidities of PCOS in adolescents. Holistic treatment and concern for related comorbidities should ideally begin as early as possible in obese adolescents once the diagnosis of PCOS is confirmed. CONCLUSION: Adolescents with PCOS and obesity need more attention from physicians and researchers, and the effective interventions in the early stage are critical to improve their life quality.